2021
DOI: 10.1002/lary.29945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Strength of Evidence of Pediatric Otolaryngology Research Literature: A 20‐Year Review

Abstract: Objectives/Hypothesis: Quantity and quality of Otolaryngology-Head and Neck Surgery (OTL-HNS) research are increasing, yet patterns within Pediatric OTL-HNS publications are unknown. This study examines trends in the level of evidence of pediatric OTL-HNS articles over a 20-year period to quantify the growth and characterize contributing factors.Study Design: Review article. Methods: A retrospective review was conducted on 12 peer-reviewed OTL-HNS journals at three time-points: 1996, 2006, and 2016. Pediatric-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Furthermore, there is a significant increase in pediatric OHNS articles published in the journal. Our findings are consistent with a recent Canadian review which showed a greater absolute number of pediatric OHNS articles published over 20 years [ 20 ]. Another Canadian study demonstrated that Pediatric OHNS was heavily represented among program directors, and may be partially explained by differences in remuneration.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there is a significant increase in pediatric OHNS articles published in the journal. Our findings are consistent with a recent Canadian review which showed a greater absolute number of pediatric OHNS articles published over 20 years [ 20 ]. Another Canadian study demonstrated that Pediatric OHNS was heavily represented among program directors, and may be partially explained by differences in remuneration.…”
Section: Discussionsupporting
confidence: 93%
“…Results from high LOE studies tend to be more reliable and reproducible in clinical practices [ [5] , [6] , [7] ]. A review of the LOE of articles published in biomedical journals has produced contrasting outcomes, with some journals showing improvement, whereas others remained static [ [8] , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%